STEPS FOR DETERMINING THE SLOPE ANGLE OF AN OPEN MINE (American Journal of Interdisciplinary Research and Development, 2023)
Open pit mining is defined as the method of extracting any near surface ore deposit using one or more horizontal benches to extract the ore while dumping overburden and tailings (waste) at a specified disposal site outside the final pit boundary. Open pit mining is used for the extraction of both metallic and nonmetallic ores. Open pit mining is considered different from quarrying in the sense that it selectively extracts ore rather than an aggregate or a dimensional stone product. A new Mine Slope Instability Index (MSII) to assess the (in)stability conditions of slopes in open-pitmining is presented. Eighteen parameters that can be easily obtained and rated in the field, and that areimportant for open-pit slope stability, are employed for the MSII definition. Their corresponding ratings are also proposed, so that the MSII can be computed as a simple weighted sum of ratings for all parameters considered; to minimize subjectivity the weights are computed, in the context of the Rock Engineering Systems paradigm, using an optimized Back-Propagation Artificial Neural Network that has been trained with an extensive database of worldwide open-pit slope stability case histories. Results show that the ANN provides a highly reliable RES interaction matrix, and also that the selected parameters are important for open-pit slope stability. Slope (in)stability hazard levels are defined based on MSII values and the predictions of the newly proposed MSII are validated by comparing our predictions with the actual (i.e. observed) behaviour corresponding to 12 independent case histories that were not used for the ANN training. An excellent agreement between predictions and observations has been found, with only one (out of 12) cases providing an incorrect prediction.